1981
DOI: 10.1152/jappl.1981.51.5.1183
|View full text |Cite
|
Sign up to set email alerts
|

Tritiated water for estimating total body water and water turnover rate in birds

Abstract: The use of tritiated water (TOH) to estimate total body water (TBW) and total water turnover rate was validated in chukar partridges (Alectoris chukar) and sand partridges (Ammoperdix heyi). For six chukar partridges weighing between 315 to 475 g, TOH equilibration with body fluids was less than 45 min after intramuscular or intravenous injections. Mean TOH space in eight chukar partridges was 99.8% of the mean TBW measured by desiccation with individuals ranging between 97.9 and 103.2%. TOH space best approxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
42
0

Year Published

1983
1983
2006
2006

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 0 publications
3
42
0
Order By: Relevance
“…After blood sampling, the bird was then placed back into its run. Previous research has shown that 120 min is sufficient for HTO to equilibrate with body water in birds (Degen et al 1981;Gales 1989;Kirkwood and Robertson 1997;Shaffer et al 2001b). Therefore, we were con fident that isotopic water had completely mixed with the gulls' body water.…”
Section: Isotopic Water Administration Sampling and Analysismentioning
confidence: 99%
See 4 more Smart Citations
“…After blood sampling, the bird was then placed back into its run. Previous research has shown that 120 min is sufficient for HTO to equilibrate with body water in birds (Degen et al 1981;Gales 1989;Kirkwood and Robertson 1997;Shaffer et al 2001b). Therefore, we were con fident that isotopic water had completely mixed with the gulls' body water.…”
Section: Isotopic Water Administration Sampling and Analysismentioning
confidence: 99%
“…Specific activity of tritiated body water was determined in trip licate by scintillation spectrometry (Beckman LS 6500, Beckman Coulter, Fullerton, CA) of water obtained from serum using the freeze-trap method (Ortiz et al 1978). TBW (g) was calculated from the initial and final dilution of isotopic water injected into a bird (Degen et al 1981). Total water influx (TWI) and efflux (TWE) were calculated from the turnover of isotopic water using Equations (4) and (6) of Nagy and Costa (1980), assuming a linear change in body mass.…”
Section: Isotopic Water Administration Sampling and Analysismentioning
confidence: 99%
See 3 more Smart Citations